Pembinaan Warga Gereja Methodis Injili Bandung dalam Menghadapi Pandemi Covid-19 - Junihot M. Simanjuntak; Duma Pakpahan; Glorya Eugene Pumpente (Unika Santu Paulus Ruteng, 2022)
The purpose of this service aims to explain the urgency and impartiality of Christology teaching as the main teaching material in fostering the faith of the congregation during the Covid-19 pandemic The importance of this coaching activity is because it is hoped that all members of the Bandung Evangelical Methodist Church will know more about the God who gives hope in Jesus Christ during the Covid-19 pandemic, and so that they will be better prepared to face the COVID-19 pandemic after Christology teaching materials are taught. It is also hoped that all members of the congregation who are fostered will be able to gain new experiences and knowledge. This action takes the form of assisting members of the Evangelical Methodist Church with faith-building activities. This activity is carried out with the method of mentoring learning through teaching and counseling. The results of the mentoring activities were 1) 69.8% of the congregation needed Christology teaching materials because they wanted to know more about the God who gives hope in Jesus Christ during the Covid-19 pandemic and 2) The response of the congregation after teaching the congregation was more prepared to face the covid-19 pandemic because they believed that Christ the Immanuel was with the congregation